Sistem Presensi Pegawai Berbasis Digital Signatures Dan Gps Location - Damanik, Abdi Rahim; Hartama, Dedy; Sumarno, Sumarno; Gunawan, Indra (Dike, 2023)
Digital signatures (Digital Signatures) is one of the authentication used by the user to add a verification that acts as a signature. In this study, the data collection process in the form of signatures by the user will be carried out to carry out employee attendance on every working day. The attendance process that is being carried out at STIKOM Tunas Bangsa still uses manual signatures which are very less effective in the data recording process. Technological advances both in terms of programming and web coding are one of the keys in the process of using digital signatures and a solution to facilitate employees in the employee attendance process. Digital signature documents are used to maintain the authenticity of the document as a whole. The authentication process is applied as a proof of the authenticity of digital-based signatures. If the digital-based signature is original, the digital-type file is still original and the owner is a legitimate person, with digitally signed and online verification that will make it easier both in terms of use and security of the employee attendance process. The application of GPS Location is useful for finding and storing location data for each employee when carrying out online attendance.